Potential of Drug Efficacy Evaluation in Lung and Kidney Cancer Models Using Organ-on-a-Chip Technology - Seong-Hye Hwang; Sangchul Lee; Jee Yoon Park; Jessie Sungyun Jeon; Young-Jae Cho; Sejoong Kim (Micromachines, 2021)
Organ-on-a-chip (OoC) is an exponential technology with the potential to revolutionize disease, toxicology research, and drug discovery. Recent advances in OoC could be utilized for drug screening in disease models to evaluate the efficacy of new therapies and support new tools for the understanding of disease mechanisms. Rigorous validation of this technology is required to determine whether OoC models may represent human-relevant physiology and predict clinical outcomes in target disease models. Achievements in the OoC field could reveal exciting new avenues for drug development and discovery. This review attempts to highlight the benefits of OoC as per our understanding of the cellular and molecular pathways in lung and kidney cancer models, and discusses the challenges in evaluating drug efficacy.